2019
DOI: 10.1111/jvim.15583
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings, diagnostic test results, and treatment outcome in cats with hiatal hernia: 31 cases (1995‐2018)

Abstract: Background Information regarding clinical signs, assessment, treatment, and outcome in cats with hiatal hernia (HH) is limited. Objectives To characterize the clinical presentation of HH and medical and surgical outcomes in a cohort of affected cats. Animals Thirty‐one client‐owned cats with HH. Methods Medical records of cats with HH were retrospectively reviewed for signalment, history, results of diagnostic tests, details of surgical and medical treatments, complications, and outcome. Long‐term follow‐up da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 29 publications
2
32
1
Order By: Relevance
“…[1][2][3] These abnormalities result in variable amounts of respiratory distress, stertor/stridor, exercise intolerance, and other cranio facial and gastrointestinal health problems. [3][4][5] In brachy cephalic cats, particularly Persian cats and exotic breeds, brachycephalic abnormalities have been seen but few clinical reports have been published. 4,6 In 2012, Corgozihno et al 6 documented a soft palate elongation in a Persian cat presenting with recurrent epi sodes of respiratory distress and pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These abnormalities result in variable amounts of respiratory distress, stertor/stridor, exercise intolerance, and other cranio facial and gastrointestinal health problems. [3][4][5] In brachy cephalic cats, particularly Persian cats and exotic breeds, brachycephalic abnormalities have been seen but few clinical reports have been published. 4,6 In 2012, Corgozihno et al 6 documented a soft palate elongation in a Persian cat presenting with recurrent epi sodes of respiratory distress and pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs in our study were 29 months of age, which is older than the age reported in most of the studies. [1][2][3][4][5][6]11,19 The two large breed dogs in our study were 151 and 125 months of age at the time of surgery, explaining the difference with our small sample. Correction of the upper airway was not always attempted first in the brachycephalic breeds, following Mayhew et al 5 Fifty percent of the cases were converted to an open laparotomy.…”
Section: Discussionmentioning
confidence: 79%
“…Most of our cases involved brachycephalic dogs, similarly to cases reported in previous studies. [1][2][3][4][5][6]11,19 Two large breed dogs were presented for chronic gastroesophageal refluxes that were not responding to medical treatment. Dogs in our study were 29 months of age, which is older than the age reported in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations